From Awareness to Action: The Five Mindfulness Trainings as a Pillar of Sustainable Modern Buddhist Life Amid the Global Climate Crisis - Liau, Yusmiati; Bi, Troi Dao (LPPM STIAB JINARAKKHITA LAMPUNG, 2025)
This study examines the contribution of Buddhist ethics, particularly the Pañcasīla and the Five Mindfulness Trainings (FMT), as a moral and practical framework for addressing the global climate crisis. The research applies a literature study with a qualitative descriptive approach, analyzing Buddhist texts, academic works, and prior studies on mindfulness and ecology. The findings highlight that Buddhist teachings stress the transformation of greed, hatred, and ignorance as the roots of ecological degradation. Five operational indicators are identified: ecological awareness through mindfulness, universal compassion, restraint of greed through simple living, intergenerational responsibility, and inner transformation toward sustainable behavior. The FMT reinforces these indicators with practical applications such as mindful consumption, nonviolent lifestyles, responsible communication, and ecological solidarity. The study concludes that Buddhism can be operationalized as a global ethic that guides lifestyle changes at both individual and community levels toward sustainability.